2010
DOI: 10.1038/ijir.2010.8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of vascular smooth muscle and corpus cavernosum on hypercholesterolemia. Is resveratrol promising on erectile dysfunction?

Abstract: The aim of this study is to evaluate the effects of hypercholesterolemia in thoracic aorta (TA), mesenteric artery (MA), renal artery (RA), and corpus cavernosum (CC) isolated from cholesterolfed rabbits. For determination of the maximum detrimental effect, vasorelaxation and vasoconstriction results of arteries and CC have been compared. Animals were fed with a diet that contained 2% w/w cholesterol and 2% w/w high cholesterol plus resveratrol (4 mg kg -1 per day) for 6-week duration. Total cholesterol levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…Although RVT activates eNOS and restores impaired relaxation to NO in aorta [19,28,29], in line with our studies, a recent paper also found ACh‐induced relaxation was not increased by RVT in MCC [13]. This may be due to tissue‐specific effect of RVT on eNOS activation as suggested by Muller and colleagues, since L‐NAME inhibited RVT‐induced relaxation in aorta but not in pulmonary artery [30] or due to prevailing pathological condition as RVT restores impaired ACh‐induced relaxation in hypercholesterolemic rabbit corpus cavernosum [8,11,12] or spontaneous hypertensive rat aorta [31].…”
Section: Discussionsupporting
confidence: 90%
“…Although RVT activates eNOS and restores impaired relaxation to NO in aorta [19,28,29], in line with our studies, a recent paper also found ACh‐induced relaxation was not increased by RVT in MCC [13]. This may be due to tissue‐specific effect of RVT on eNOS activation as suggested by Muller and colleagues, since L‐NAME inhibited RVT‐induced relaxation in aorta but not in pulmonary artery [30] or due to prevailing pathological condition as RVT restores impaired ACh‐induced relaxation in hypercholesterolemic rabbit corpus cavernosum [8,11,12] or spontaneous hypertensive rat aorta [31].…”
Section: Discussionsupporting
confidence: 90%
“…RSV treatment might improve erectile dysfunction induced by hypercholesterolemia, with increased vasorelaxation responses to acetylcholine in the corpus cavernosum isolated from cholesterol-fed male rabbits [339]. However, it may be necessary to be cautious about intake RSV during pregnancy.…”
Section: Reproductive System Diseasesmentioning
confidence: 99%
“…We demonstrated that a 2% high cholesterol diet for 6 weeks significantly impaired cavernosal relaxation responses. Endothelium-dependent relaxation responses induced by acetylcholine were significantly higher in the control and resveratrol groups when compared with the hypercholesterolemia group in that study (15). In this preliminary study, we evaluated cavernosal eNOS expression in three groups with the same experimental model and determined that mean eNOS expression levels in the resveratrol and control groups were significantly higher than that in the hypercholesterolemia group.…”
Section: Controlmentioning
confidence: 99%
“…The rabbits in the hypercholesterolemia and resveratrol groups were fed with a 2% (w/w) hypercholesterolemic diet and drinking water for 6 weeks. Resveratrol (Sigma Aldrich) at a daily dosage of 4 mg/kg was also administered via drinking water for the resveratrol group (15,18). All rabbits were weighed at the beginning and the end of the study.…”
Section: Experimental Animals and Hypercholesterolemia Conditioningmentioning
confidence: 99%
See 1 more Smart Citation